Gestión de inventarios en la compañía Massline de Almacenes Shineray, en la ciudad de Babahoyo, periodo 2023. - Albario Obando, Zaida Jamilexi (2024)
The following case study will be an analysis of the inventory control and management that is carried in the company Massline S.A, in the period 2023 where the company is dedicated to the marketing of motorcycle parts of the Shineray brand, since in that period inconsistencies such as inventory management are carried, leading to the loss of accurate information about the stock of products as they are quick sale and greater acquisition by customers, given the erroneous information is impossible for the administrator to make decisions because it does not have a detailed report of the inputs and outputs of the goods. A relevant factor is the reality of the company both in the administrative and commercial part since for the knowledge of the situation an interview with the administrator of the company will be carried out in order to gather information of all the detected problems arriving to a conclusion that are taken with the objectives that are mentioned leaving behind the traditional form and adapting to the present time implementing automated computer systems for the decision making and optimizing processes and influencing the generation of employment in the city.